Exploring Italian healthcare facilities response to COVID-19 pandemic: Lessons learned from the Italian Response to COVID-19 initiative - Parotto, Emanuela; Lamberti-Castronuovo, Alessandro; Censi, Veronica; Valente, Martina; Atzori, Andrea; Ragazzoni, Luca (Frontiers in Public Health, 2023)
The COVID-19 pandemic exerted an extraordinary pressure on the Italian's healthcare system (Sistema Sanitario Nazionale, SSN), determining an unprecedented health crisis. In this context, a multidisciplinary non-governmental initiative called Italian Response to COVID-19 (IRC-19) was implemented from June 2020 to August 2021 to support the Italian health system through multiple activities aimed to mitigate the effects of the pandemic. The objective of this study was to shed light on the role of NGOs in supporting the SSN during the first pandemic wave by specifically exploring: 1) the main challenges experienced by Italian hospitals and out-of-hospital care facilities and 2) the nature and extent of the IRC-19 interventions specifically implemented to support healthcare facilities, to find out if and how such interventions met healthcare facilities’ perceived needs at the beginning of the pandemic. Health facilities’ main challenges concerned three main areas: healthcare workers, patients, and facilities’ structural changes. The IRC-19 initiative contributed to support both hospital and out-of-hospital healthcare facilities by implementing interventions for staff and patients’ safety and flow management and interventions focused on the humanization of care. The support from the third sector emerged as an added value that strengthened the Italian response to the COVID-19 pandemic. This is in line with the Health - Emergency and Disaster Risk Management (H-EDRM) precepts, that call for a multisectoral and multidisciplinary collaboration for an effective disaster management.